Humor på alvor i litteraturundervisninga med «Anekdote» av Herman Wildenvey - Røskeland, Marianne (Nordlit, 2022)
This article studies the potential of paying attention to humour in texts in teaching literature. It is based on different approaches to the poem «Anekdote» (1911) by the Norwegian author Herman Wildenvey. The article is inspired by discussions with teacher students about the humour in the poem. Central questions are whether the poem is funny or not and, if it is funny, what or whom do we laugh at? And also: How can this poem be read in the literature class? Different answers to these questions are discussed in light of theories of humour. The article discusses how different approaches to the humour in the poem imply different interpretations of it. It is of particular interest to study values and moral attitudes that the poem may convey, and to reflect on the role of humour in this aspect. Humour may serve different functions and is not always controllable, but it is often linked to the ambiguity of language. Finally, the article argues for valuing reflections on humour in litterature teaching, both in teacher training and in schools.